Wavelet analysis for Mueller matrix images of biological crystal networks - Ushenko, Yu.O.; Tomka, Yu.Ya.; Pridiy, O.G.; Motrich, A.V.; Dubolazov, O.V.; Misevitch, I.Z.; Istratiy, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Theoretically grounded in this work is the efficiency of using the statistical and fractal analyses for distributions of wavelet coefficients for Mueller-matrix images of biological crystal networks inherent to human tissues. The authors found interrelations between statistical moments and power spectra for distributions of wavelet coefficients as well as orientation-phase changes in networks of biological crystals. Also determined are criteria for statistical and fractal diagnostics of changes in the birefringent structure of biological crystal network, which corresponds to pathological changes in tissues.